IDENTIFICATION OF PALYNOZONES AND AGE EVALUATION OF ZUBAIR FORMATION, SOUTHERN IRAQ - Al-Obaidi, Ryadh Younis Kassim (Al-Nahrain Journal of Science, 2018)
Fourteen rock selected samples from lower and middle parts of Zubair Formation in Zubair 109 (Zb-109) and Zubair 43 (Zb-43) boreholes of Zubair oil field at southern Iraq, they have been subjected to standard palynological processing techniques were used to extract the acid resistant organic matter. Microscopic analysis of the sedimentary organic matter of the two boreholes revealed abundant and diverse palynomorphs of (35) species of spores belonging to (23) genera, (9) species of pollen grains belonging to (6) genera and (21) species of dinoflagellate cysts belonging to (13) genera.Two assemblage palynozones have been also identified based on the index palynomorphs contained in each zone. The age assignment of each palynozone is based on international correlation with Australia, Middle East and Europe countries.